SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Uncertainty sources for measurable ocean carbonate chemistry variables - Brendan R. Carter; Jonathan D. Sharp; Andrew G. Dickson; Marta Álvarez; Michael B. Fong; Maribel I. García‐Ibáñez; Ryan J. Woosley; Yuichiro Takeshita; Leticia Barbero; Robert H. Byrne; Wei‐Jun Cai; Melissa Chierici; et al. (Limnology and Oceanography, 2024)
The ocean carbonate system is critical to monitor because it plays a major role in regulating Earth's climate and marine ecosystems. It is monitored using a variety of measurements, and it is commonly understood that all components of seawater carbonate chemistry can be calculated when at least two carbonate system variables are measured. However, several recent studies have highlighted systematic discrepancies between calculated and directly measured carbonate chemistry variables and these discrepancies have large implications for efforts to measure and quantify the changing ocean carbon cycle. Given this, the Ocean Carbonate System Intercomparison Forum (OCSIF) was formed as a working group through the Ocean Carbon and Biogeochemistry program to coordinate and recommend research to quantify and/or reduce uncertainties and disagreements in measurable seawater carbonate system measurements and calculations, identify unknown or overlooked sources of these uncertainties, and provide recommendations for making progress on community efforts despite these uncertainties. With this paper we aim to (1) summarize recent progress toward quantifying and reducing carbonate system uncertainties; (2) advocate for research to further reduce and better quantify carbonate system measurement uncertainties; (3) present a small amount of new data, metadata, and analysis related to uncertainties in carbonate system measurements; and (4) restate and explain the rationales behind several OCSIF recommendations. We focus on open ocean carbonate chemistry, and caution that the considerations we discuss become further complicated in coastal, estuarine, and sedimentary environments.

Best Practice Data Standards for Discrete Chemical Oceanographic Observations - Li-Qing Jiang; Denis Pierrot; Rik Wanninkhof; Richard A. Feely; Bronte Tilbrook; Simone Alin; Leticia Barbero; Robert H. Byrne; Brendan R. Carter; Andrew G. Dickson; Jean-Pierre Gattuso; Dana Greeley; et al. (Frontiers in Marine Science, 2022)
Effective data management plays a key role in oceanographic research as cruise-based data, collected from different laboratories and expeditions, are commonly compiled to investigate regional to global oceanographic processes. Here we describe new and updated best practice data standards for discrete chemical oceanographic observations, specifically those dealing with column header abbreviations, quality control flags, missing value indicators, and standardized calculation of certain properties. These data standards have been developed with the goals of improving the current practices of the scientific community and promoting their international usage. These guidelines are intended to standardize data files for data sharing and submission into permanent archives. They will facilitate future quality control and synthesis efforts and lead to better data interpretation. In turn, this will promote research in ocean biogeochemistry, such as studies of carbon cycling and ocean acidification, on regional to global scales. These best practice standards are not mandatory. Agencies, institutes, universities, or research vessels can continue using different data standards if it is important for them to maintain historical consistency. However, it is hoped that they will be adopted as widely as possible to facilitate consistency and to achieve the goals stated above.

Anomalous Biogeochemical Response to a Flooding Event in the Delaware Estuary: A Possible Typology Shift Due to Climate Change - Yoana G. Voynova; Jonathan H. Sharp (Estuaries and Coasts, 2012)

Estuarine oxygen dynamics: What can we learn about hypoxia from long‐time records in the Delaware Estuary? - Jonathan H. Sharp (Limnology and Oceanography, 2010)
Hypoxia and anoxia occurred in the upper Delaware Estuary throughout much of the 20th century and diminished over the past several decades. I reviewed 30 yr of data from my laboratory's research efforts, 40 yr of consistent monitoring data from a multistate agency, results from inconsistent data collection from the past century, and anecdotal information to construct a long‐time picture of the decline and increase of dissolved oxygen concentrations (DO) in the urban region of the estuary. The primary cause of the DO decline appeared to be inputs or allochthonous materials from urban sources (reduced nitrogen and carbon). In spite of extremely high nutrient concentrations, excess algal production did not influence DO anywhere along the tidal freshwater stretch or the saline portion of the well‐mixed Delaware Estuary; and it does not have an influence today. The nutrient loading to the Delaware Estuary is very high, yet the typical signs of eutrophication are not obvious. Based on a model of apparent oxygen utilization, the Delaware Bay apparently had higher primary production 50 yr ago, a time when nutrient concentrations were as high or higher than today, shellfish and finfish production were apparently also higher, and DO was close to saturation. This analysis is offered as guidance in assessing and managing estuarine eutrophication, which is too often considered narrowly to be the result of inadvertent overfertilization by nutrients or a single nutrient element.

A Biogeochemical View of Estuarine Eutrophication: Seasonal and Spatial Trends and Correlations in the Delaware Estuary - Jonathan H. Sharp; Kohei Yoshiyama; Alexander E. Parker; Matthew C. Schwartz; Susan E. Curless; Allison Y. Beauregard; Justin E. Ossolinski; Allen R. Davis (Estuaries and Coasts, 2009)

Phytoplankton response to nutrient enrichment in an urbanized estuary: Apparent inhibition of primary production by overeutrophication - Kohei Yoshiyama; Jonathan H. Sharp (Limnology and Oceanography, 2006)
Phytoplankton response to nutrients was examined with a 26‐yr database from the Delaware Estuary. Biomassnormalized primary production did not increase linearly with increasing nutrient concentrations and instead showed saturation at comparatively low nutrient concentrations and decreased at high concentrations. To separate the effects of light availability and temperature on primary production from those of other environmental variables, we developed an empirical model of areal primary production. The model equation was obtained for the entire dataset and the effect of the residual variables was expressed as correction factors of observed primary production to the model estimates. The model accounted for 67% of variability of observed primary production overall, indicating that production of the estuary was mainly controlled by light availability and temperature. In contrast, a similar model applied to a Chesapeake Bay database had shown a poorer fit, indicating consistent light limitation in the Delaware Estuary and varying strengths of light and nutrient limitation in the Chesapeake Bay. The relationships between nutrients and correction factors for the Delaware Estuary showed that the model underestimates primary production at low and mid nutrient concentrations and overestimates it at high concentrations. The model fit and correction factors for five regions of the estuary indicate a high‐nutrient, low‐growth situation in the Delaware Estuary because of varying influences of light limitation, proportions of nutrients, and probably toxic contaminants in areas with large anthropogenic inputs—including high nutrients.

In situ feeding and element removal in the symbiont‐bearing sponge Theonella swinhoei : Bulk DOC is the major source for carbon - Gitai Yahel; Jonathan H. Sharp; Dominique Marie; Clivia Häse2; Amatzia Genin (Limnology and Oceanography, 2003)
The vast majority of organic matter in the world ocean is found in the dissolved pool. However, no evidence has been demonstrated for direct uptake of bulk dissolved organic matter (DOM) by organisms other than bacteria and some invertebrate larvae. The total organic carbon (TOC) is 10—30% higher in coral reefs than in adjacent open waters. The dissolved organic carbon (DOC) accounts for >90% of the TOC. Using a new in situ technique for clean sampling of the seawater inhaled and exhaled by benthic suspension feeders, we measured directly the removal of DOC in the symbiont‐bearing reef sponge Theonella swinhoei . The sponge removed up to 26% (± SD: 12% ± 8%) of the TOC (dissolved and particulate) from the water it filtered during a single passage through its filtration system. Most of the carbon gained by the sponge was from the dissolved pool (10 ± 7 µmol C L −1 ), an order of magnitude greater than the carbon gained from the total living cells (phytoplankton and bacteria) the sponge removed (2 ± 1 µmol C L ‐ ). In T. swinhoei , over two‐thirds of the sponge biomass consists of symbiotic bacteria, which likely play an important role in DOC uptake. Our findings indicate that the role of DOC in metazoan nutrition and the role of metazoans in DOC cycling may have been grossly underestimated.